Flyte - Sage, Angie; Zug, Mark (New York : Katherine Tegen Books, 2006)
When Princess Jenna is pursued by a dark wizard, it is the apprentice, Septimus Heap, who must save her while enduring such terrors as a night in the Forest with hungry wolverines and carnivorous trees.
Keywords: Princesses -- Fiction; Wizards -- Fiction; Magic -- Fiction; Fantasy